Lychee peel extract attenuates depression-like behavior in a rat model of chronic restraint stress - Wathita Phachonpai, Watcharaporn Preedapirom, Kitipong Wuthiyan, Anukul Junkaew, Terdthai Tongun (Journal of Applied Pharmaceutical Science, 2024)
The utilization of vegetable or fruit by-products as functional foods to protect against several diseases, including depression, has gained great interest. Litchi chinensis Sonn. (lychee; LC) peel is considered an important source of polyphenols, which could be beneficial for mental health. We investigated the antidepressant effect and possible mechanisms of LC peel extract in a rat model of chronic restraint stress (CRS). Five groups of male rats were used: naïve control, vehicle (distilled water) + stress, fluoxetine 20 mg/kg + stress, LC peel extract 150 mg/kg + stress, and LC peel extract 300 mg/kg + stress. All groups except the naïve control were exposed to CRS (6 hours/day for 56 days) to induce depression-like activity. Only the high dose of LC peel extract exerted an antidepressant effect on the rat’s behavior patterns in both the tail suspension (p < 0.001) and forced swimming (p < 0.001) tests, restored brain serotonin levels (p < 0.001), decreased lipid peroxidation (p < 0.05), improved superoxide dismutase activity (p < 0.001), and reduced plasma corticosterone (CORT) (p < 0.05). This study provides the first evidence that an ethanolic extract of LC peel possesses antidepressant activity mediated by its antioxidant effect, regulating the CORT hormone and normalizing serotonin concentrations.
Keywords: Lychee peel, antidepressant, stress, depression, antioxidant